MEDIA EDUCATION: GLOBAL PROSPECTS AND DEVELOPMENTS IN UKRAINE (ON THE EXPAMPLE OF THE IREX “LEARN AND DISTINGUISH” PROJECT) - Lokshyna, Olena; Prykhodkina, Nataliia (Studies in Comparative Education, 2020)
The paper highlights the strategic guidelines for the media education development outlined by international organizations (UNESCO, EU). The authors analyse the implementation of media education in Ukraine. The authors analyse the implementation of the media education in the Ukrainian education starting from the adoption of the Concept on the Implementation of Media Education in Ukraine (2010). The implementation of media education into the secondary education is confirmed by example of the State Standard of Primary Education (2018) and Typical Educational Programmes for 1st-2nd and 3rd-4th grades developed under guidance of O Savchenko (2019). The authors analyse the findings of the project “Learn and Distinguish” (L2D), implemented by the International Research & Exchanges Board (IREX) in partnership with the Academy of Ukrainian Press and StopFake aimed at integrating media and information literacy skills into curricula. It was piloted in 50 schools in Ukraine, reaching approximately 5,425 students in 8th and 9th grades. The authors made conclusions that value of the L2D lies in transferring the participants’ media knowledge. No less important is the project’s input into capacity development. The authors underline the added value of the project. It promotes further harmonization of the Ukrainian education with the trends/standards of the world community providing the development of the efficient media education system in Ukraine. And secondly, it serves for the dissemination of innovative knowledge and practices at the horizontal level (between teachers, schools, students).